Ethnomedicinal plants of Shankaracharya Hill, Srinagar, J&K, India. (21st July 2015) - Kumar, Kewal; Sharma, Yash Pal; Manhas, R.K.; Bhatia, Harpreet
Abstract: Ethnopharmacological relevance: Primitive human societies have always relied on plants and plant products for various remedies. In certain areas, these folk medical prescriptions are endemic and have survived through ages from one generation to the next through word of mouth. They do not exist as written knowledge. The present study was undertaken with an objective of documenting the ethnobotanical information of medicinal plants of Shankaracharya Hill by taking the help of local herbalists, elderly and knowledgeable people. Material and methods: The data was quantitatively analysed using use-value (UV), informant consensus factor (ICF) and fidelity level (Fl%) indices. Results: Total 130 plant species from 57 families and 111 genera were ethno-medicinally utilized by the 103 informants interviewed in the present study. The most used families were Asteraceae, Rosaceae, Lamiaceae, Fabaceae and Brassicaceae. The medicinal plants were mainly herbs (79.2%). Leaves were the most used (27.6%) plant part followed by whole plant (14.8%), root (11.4%) and seed (10.5%). The most important species on the basis of UV were Viola odorata, Taraxacum campylodes, Aesculus hippocastanum, Artemisia absinthium, Daucus carota, Thymus serphyllum, Ephedra gerardiana and Salvia moorcroftiana . The values ICF ranged between 0.93 and 0.76. Only Epilobium hirsutum recorded 100% Fl. Some of the most important medicinal plants with high Fl values were Tribulus terrestris, Asparagus officinalis, Trifolium repens, Anemone biflora, Melia azedarach, A. absinthium, Lonicera quinquelocularis, Rosa webbiana, D. carota, Oxalis corniculata and Potentilla reptans . Conclusion: The contribution of plant parts collected through destructive methods was 29.5%. Harvesting of roots, rhizomes, bulbs and corm kills the parent plant and could be a severe threat for survival of the often rare and slowly reproducing medicinal plants, and therefore need sustainable utilization and conservation strategies. Ethnomedicinal species like A. absinthium, A. hippocastanum, D. carota, M. azedarach, T. campylodes, T. serphyllum, T. terrestris having high number of citations, UV and FL should be analyzed for phytochemicals and pharmacology. Graphical abstract: